Malignant external otitis: about 50 cases at Fann hospital center - Diouf, Mame Sanou; Barry, Mouhamed; Ndiaye, Moustapha; Tall, Abdourahmane; Ndiaye, Ciré; Ndiaye, Malick; Niang, Fallou; Niang, Cheikh Diène; Fall, Faty (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Malignant external otitis (MEO) is an osteitis of the skull base, originating in the external auditory canal. It is most common in elderly and diabetic patients. Early management prevents complications. The objective of the study is to provide an epidemiological, clinical, paraclinical, therapeutic and evolutionary profile. Methods: From January 2010 to January 2021, we carried out a retrospective study in the ENT department of Fann hospital, selecting the patients hospitalized and suffering from malignant external otitis Results: Fifty patients were included in this study. The mean age was 65, with a sex ratio (M/F) of 1.5. Forty-six patients were diabetic; 2 patients had leukemia and 2 had no previous history. The average length of hospital stay was 3 months. The reasons for consultation were otalgia, otorrhea and deafness in 96%, 80% and 32% respectively. Examination revealed otorrhea in 58%, peripheral facial paralysis in 54% and a polyp in 80%. Ear swab analysis isolated Pseudomonas aeruginosa in 28%. CT scan showed ear cavity filling in 40 cases and bone lysis in 26. Antibiotic treatment was based on ciprofloxacin or ofloxacin in 44% of cases, and the combination of ceftriaxone-ciprofloxacin or ofloxacin in 44%. The average duration of treatment was 3 months. There were 12% recurrences and 2 cases of death after an average follow-up of 10 months. Conclusions: MEO is a rare pathology that occurs more frequently in elderly subjects with immunodepressive backgrounds. Antibiotic therapy has proved effective in treating this condition.